Analisis Efektivitas Sistem Alarm Pada Distributed Control System (DCS) Dalam Mendukung Keandalan Operasi Industri - Dery Irawan (JOURNAL SAINS STUDENT RESEARCH, 2026)
A distributed control system (DCS) is the backbone of modern process facility operations, but the complexity and the sheer number of control signals often trigger alarm floods, causing operators to receive a large number of alarms in a short time, which reduces alertness and decision-making ability. This study aims to analyze the effectiveness of the alarm system in a DCS at a processing facility with reference to the ANSI/ISA-18.2 standard, and to evaluate its impact on operational reliability. The research method combines quantitative analysis of six months of historical alarm logs—divided into pre-implementation (baseline) and post-implementation of alarm rationalization phases—with a qualitative assessment of operator workload. The results show that under initial conditions, the average alarm reached 45 alarms per hour per operator, far exceeding the recommended limit (<6 alarms per hour). After implementing rationalization actions, including adjusting the deadband, setting on-delay and off-delay timers, and reorganizing alarm priorities, the number of alarms was successfully reduced by 78% to an average of 9.8 alarms per hour. The significant reduction in nuisance and chattering alarms correlated with a 42% increase in operator response time to critical alarms. These findings indicate that systematic, standardized, and continuous alarm management not only reduces the cognitive load on operators but also lowers the probability of unplanned shutdowns, thereby contributing to improved reliability, safety, and operational efficiency in processing facilities.